COMPARING THE USE OF NON-VERBAL COMMUNICATION IN CERTAIN ‘FOOD’ AND ‘FASHION’ VIDEOS ON THE VOGUE YOUTUBE CHANNEL - Mahnasari, Suriatni Irnah; Mahmud, Murni (Journal of English Literature and Linguistic Studies, 2024)
This research discusses comparing the use of non-verbal communication in certain ‘food’ and ‘fashion’ videos on the vogue youtube channel. This research aims to analyze the types of non-verbal communication in ‘Florence Pugh Eats 11 English Dishes – Mukbang | Vogue’ and ‘Every Outfit Euphoria’s Barbie Ferreira Wears in a Week | 7 Days, 7 Looks | Vogue’ videos and compare them using Eaves and Leathers theory (2018). The research method used in this study is a qualitative descriptive method. The data are taken from ‘Florence Pugh Eats 11 English Dishes – Mukbang | Vogue’ and ‘Every Outfit Euphoria’s Barbie Ferreira Wears in a Week | 7 Days, 7 Looks | Vogue’ videos. In this research, there are 126 data that shows the results of the research.  The types of non-verbal communication found in Florence Pugh Mukbang video are Facial Expression, Eye Behaviors, Bodily Communication and Vocalic Communication. Meanwhile the types of non-verbal communication found in Barbie Ferreira Fashion – Outfit videos are Facial Expression, Eye Behaviors, Bodily Communication, Personal Appearance, and Vocalic Communication.